An Association between Breaking Voice and Grief-related Lyrics in Country Music - Brandon Paul; David Huron (Empirical Musicology Review, 2010)
Thirty-one instances of breaking voice were identified in recordings of Country songs. Song lyrics were rated by independent judges for grief-related content in both breaking-voice songs and matched control songs. Judges compared pairs of lyrics for target and control songs at four context sizes: entire sets of lyrics, single stanzas, isolated lines, and individual words where the breaking voice occurs. An association was found between instances of breaking voice and grief-related content for individual words but not for the larger lyrical contexts. The results are consistent with the idea that breaking voice provides an affective cue conveying, evoking or highlighting grief.